Identifying the Process of Crucial Tactical Farm Management Decision-Making and Its Types - 김종선 (한국농촌경제연구원, 2011)
A significant amount of farm management decision-making (FMDM) research has been carried out in almost all areas of farm management for various purposes in many countries. However, it appears that there is a major deficiency in FMDM research in Korea. This is likely because the main interest of most researchers studying farm management is related to direct ways of improving farmers’ business performance, such as the development of crop production technology and marketing skills. Therefore, there is a need for research aimed at better understanding how Korean farmers take into account external and internal factors in the process of farm management decision-making. Such research may contribute to the formation of effective government policies and extension services and improved financial performance at the individual farm level. This study aims to identify the types and characteristics of individual farmers' crucial tactical decision-making on farm management by employing the grounded theory approach and by analysing the data gained from a mail survey.
Keywords: farm management; tactical decisions; crucial farm management-decision making; farm business performance; farm management; tactical decisions; crucial farm management-decision making; farm business performance